The Relationship between Fiber Consumption and the Incidence of Overweight in Adolescent Girls in Aceh Barat - Wardah Iskandar; Afwa Hayuningtyas; Hanif Muchdatul Ayunda; Marniati Marniati (Universitas Teuku Umar, 2022)
Nowadays, dietary fiber is no longer a modern food for teenagers in Indonesia. Dietary fiber has long been neglected as an important factor in dietary nutrition. This is due to a lack of public knowledge on the importance of consuming dietary fiber. Adolescence is a transition period from children to adult where they are easily influenced by the surrounding environment, easy to follow the latest trends where it is a determining factor for the quality of adolescents, such as the incidence of overweight in adolescents caused by lack of fiber consumption so that adolescents prefer fast food rather than fruit and vegetables. This study aims to determine the relationship between fiber consumption and the incidence of overweight in adolescent girls in Aceh Barat District. This research is a cross-sectional study with the sample of 50 adolescent girls aged 15-18 years old. Data was collected by means of a 24-hour food recall, weighing, and measuring their body height. Data analysis includes univariate and bivariate analysis with independent sample t-test. The results shows that there are 26% of adolescent girls who consume fiber well, while 76% of young women consume fiber bad. Fiber consumption affects the incidence of overweight in adolescent girls where the value of OR=13,588 (95% CI 1.591-116.032). So that fiber consumption has a 13.58 times chance of influencing adolescents girls not to be overweight.